ANALISIS EFEKTIVITAS KEMUDAHAN PENGGUNAAN MOBILE BANKING MUAMALAT DIN (DIGITAL ISLAMIC NETWORK) PADA GENERATION Z (ZOOMER) (STUDI KASUS BANK MUAMALAT KCP SERDANG) - Humairah Hajijah; Atika; Nur Ahmadi Bi Rahmani (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This study aims to evaluate the usability and user satisfaction of the Muamalat DIN Mobile Banking application among Generation Z, a cohort widely recognized as digital natives. The primary focus lies in assessing the effectiveness of the application’s features in addressing the demands of digital Islamic banking transactions. Employing a descriptive qualitative approach, data were gathered through in-depth interviews, field observations, and document analysis. The findings indicate that the application demonstrates a high level of user-friendliness, ensures transaction security, and adheres to the principles of Shariah-compliant finance. Nonetheless, to sustain user engagement and strengthen loyalty among younger generations, continuous enhancement of features and service quality emerges as a strategic imperative